2010
DOI: 10.1007/s10646-010-0574-0
|View full text |Cite
|
Sign up to set email alerts
|

Limit-test toxicity screening of selected inorganic nanoparticles to the earthworm Eisenia fetida

Abstract: The toxicity of a range of inorganic (Ag, Cu, Ni, Al(2)O(3), SiO(2), TiO(2) and ZrO(2)) nanoparticles (NP) and their corresponding metal salt or bulk metal oxide were screened for toxicity toward the earthworm Eisenia fetida using the limit-test design (1000 mg/kg). This study provides the first ecotoxicological life history trait data on earthworms for each these NPs, as well as for AgNO(3), Al(2)O(3), SiO(2), TiO(2) and ZrO(2). Significant effects were observed on survival for AgNO(3) (2.5% of controls), CuC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 27 publications
(29 reference statements)
9
94
2
2
Order By: Relevance
“…The Ag NPs had negative zeta potential and were stable in suspension [83]. These results are in accordance with the conclusion that the negative zeta potential of NPs causes repulsion to the soil, leading to a greater bioavailability.…”
Section: Silversupporting
confidence: 89%
See 2 more Smart Citations
“…The Ag NPs had negative zeta potential and were stable in suspension [83]. These results are in accordance with the conclusion that the negative zeta potential of NPs causes repulsion to the soil, leading to a greater bioavailability.…”
Section: Silversupporting
confidence: 89%
“…The accumulation of Ag seems to be greater in the earthworm E. fetida exposed to the corresponding AgNO 3 salt than from NPs [55,83]. However, extended X-ray absorption fine structure spectroscopy analysis in soil showed that Ag in earthworms exposed to Ag NPs suggests that accumulation was not caused only by the ionic form (i.e., ions dissolved from NPs), but that nondissolved particles contributed to Ag accumulation in the organisms [85].…”
Section: Silvermentioning
confidence: 96%
See 1 more Smart Citation
“…Relative to the control, ZnO-NPs decreased fertility by 72 %, whereas ZnO bulk increased the final number of offspring per cocoon by 36 %. The high fertility observed in cocoons from the ZnO bulk samples was unexpected, but similar results have been found by other investigators for different metal oxides NPs (Heckmann et al 2011). No fertility data could be obtained from the ZnCl 2 salt group due to the near absence of cocoons.…”
Section: Toxic Effects On Earthwormssupporting
confidence: 88%
“…For the nanosized material in their study, they characterized and reported the primary particle size (30 nm diameter) and crystallinity (73% anatase and 27% rutile); however, for the bulk control only the nominal diameter (40 μm) was reported, and no information regarding the crystal phase of the material was given. 12 As it has been suggested that the crystal phase of TiO 2 may be more important than particle size for predicting toxicity, 68,72 it is possible that a difference in the crystallinity of the two TiO 2 materials used may have significantly confounded their results regarding the role of particle size. Of the two main industrially relevant crystal phases of TiO 2 (anatase and rutile), evidence suggests that the anatase form used in the current study may be more toxic.…”
Section: ■ Discussionmentioning
confidence: 99%